THE IMPORTANCE OF MARKETING INSTRUMENTS FOR MARKET APPROACH AND OPERATION OF EXPORT COMPANIES - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2020)
In this paper we will show the importance and importance of the right combination of marketing instruments (products, prices, promotions and distribution) that affect the business performance of export-oriented companies. At the same time, it is indisputable that a good combination of the above mentioned marketing instruments has a stimulating influence on the movement of the basic parameters of the business of export-oriented companies. Also, each of the marketing mix instruments individually contributes to the business excellence of the company. The right combination of these instruments certainly leads to the success of the organization, but the real problem is determining what combination it is. That is, every business is in the dilemma of how much importance it attaches to some of the instruments of the marketing mix. The situation is particularly complicated by the fact that the results of the combination, that is, its success can only be viewed ex post, which is likely then. Organizations need prior key information in order for marketing instruments to act ex ante with the intention of creating the right mix of marketing mix instruments to market in a foreign market.